(881) Process control series: equipment specifications-part(II) سلسلة التحكم في العمليات: مواصفات المعدات - El-Shafei, Al Walid (The Institute of National Planning, 2025)
Despite extensive literature on process computers, reports detailing actual benefits and system costs are rare. Users of successful systems often hesitate to share detailed information due to proprietary interests and competitive concerns. When results are shared, they are typically expressed in qualitative terms or as percentages rather than absolute values, making it difficult to compare costs and benefits accurately. The limited number of published success stories is partly due to the time required for evaluation and the fact that many systems have not been operational long enough for proper assessment. Although there is a lack of transparency, existing information suggests that process computers can be profitable. Some systems provide operator guidance rather than closed-loop control, yet they still yield legitimate benefits. Reports also include analog systems where digital counterparts lack data. Readers can use available tables to perform their own evaluations of the announced benefits على الرغم من وجود أدبيات واسعة حول أجهزة الكمبيوتر الخاصة بالعمليات، إلا أن التقارير التي تفصل الفوائد الفعلية وتكاليف الأنظمة نادرة. غالبًا ما يتردد مستخدمو الأنظمة الناجحة في مشاركة معلومات مفصلة بسبب المصالح الخاصة والاعتبارات التنافسية. عندما يتم مشاركة النتائج، يتم التعبير عنها عادةً بمصطلحات نوعية أو كنسب بدلاً من قيم مطلقة، مما يجعل من الصعب مقارنة التكاليف والفوائد بدقة. العدد المحدود من قصص النجاح المنشورة يعود جزئيًا إلى الوقت المطلوب للتقييم، وكون العديد من الأنظمة لم تعمل لفترة كافية للتقييم المناسب. على الرغم من نقص الشفافية، تشير المعلومات الحالية إلى أن أجهزة الكمبيوتر الخاصة بالعمليات يمكن أن تكون مربحة. توفر بعض الأنظمة إرشادات للمشغلين بدلاً من التحكم المغلق، ومع ذلك فإنها لا تزال تحقق فوائد مشروعة. تشمل التقارير أيضًا أنظمة تماثلية حيث تفتقر الأنظمة الرقمية إلى بيانات. يمكن للقراء استخدام الجداول المتاحة لإجراء تقييمات خاصة بهم للفوائد المعلنة.